IMPLEMENTATION OF AXIOLOGICAL NORMS THROUGH STORIES IN PRESCHOOL - Enachi-Vasluianu, Luiza; Mălureanu, Flavia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The strategic goal of axiological education is the development of human personality through and for authentic values such as altruism, respect, tolerance, truth, cooperation, uprightness etc. This goal is achieved throughout the whole educational levels, either through specific or related disciplines.Axiological education must begin from preschool level (with age ranges from 3 to 6 years). At this age level, the implementation of values is efficiently done through stories which kindergarten teachers include periodically in their didactic activities. In Romania, the curriculum for preschool contains directions of action expressed through experiential domains and disciplines of study, but does not contain compulsory content. As such, kindergarten teachers can choose, according to the theme of study, the content that suits the best and include it in their activities with the preschoolers.Our research focuses on the axiological norms the kindergarten teachers consider relevant for contouring children’s personality profile. The specificity of this implementation is the use of stories, selected in accordance to children’s interests, age peculiarities, and moral values promoted. The study collected the opinions of 100 preschool teachers regarding the most often focussed on moral and behavioural values implemented through stories in the didactic activities. The research methods were the investigation based on questionnaire, the conversation and the systematic observation. The data collected were interpreted using the SPSS analysis. The results of the research could be used to increase teachers’ awareness on the necessity of imprinting a nucleus of values on preschoolers which will guide them in thought and action.